Damage localization in pressure vessel using guided wave-based techniques: Optimizing the sensor array configuration to mitigate nozzle effects. (1st January 2022) - Hu, Chaojie; Yang, Bin; Xiao, Biao; Xuan, Fu-Zhen; Xiang, Yanxun
Abstract: Ultrasonic guided waves are desirable technologies for damage monitoring in large structures such as pipes and pressure vessels since they could propagate over a long distance with low attenuation. However, due to the complex scattering of guided waves, it is a great challenge to extract the damage information when using guided wave-based techniques to monitor the pressure vessels equipped with accessories. As an attempt, we investigated the interactive behavior between guided waves and pressure vessel nozzles. Ensemble empirical mode decomposition, fast Fourier transform and ellipse-based damage localization algorithm are adopted to perform the signal processing and damage localization analysis, respectively. A sensor array configuration optimization method is presented to mitigate the nozzle effects on the propagation of guided waves. The optimal number of sensors is determined experimentally, and the sensor array placement is optimized by a Particle Swarm Optimization algorithm. The accurate experimental damage localization results in the pressure vessel and curved plate indicate the effectiveness of our methods.